2015
DOI: 10.3402/meo.v20.29702
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for the primary care clinic: an ambulatory boot camp for internal medicine interns

Abstract: IntroductionInternal medicine (IM) interns start continuity clinic with variable ambulatory training. Multiple other specialties have utilized a boot camp style curriculum to improve surgical and procedural skills, but boot camps have not been used to improve interns’ ambulatory knowledge and confidence. The authors implemented and assessed the impact of an intern ambulatory boot camp pilot on primary care knowledge, confidence, and curricular satisfaction.MethodsDuring July 2014, IM interns attended ambulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Pre-internship programmes are usually of limited duration (several hours to several weeks) and focus on the acquisition of discrete skills. Self-assessment is usually used in evaluation of these programmes [ 36 , 40 , 41 ], although some have implemented objective knowledge assessments [ 42 ]. While participants often demonstrate improved self-confidence [ 36 ], which has proven to be durable in some settings [ 40 ], other authors have not reported on the phenomenon of tempered self-confidence that we observed in a subset of our participants.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-internship programmes are usually of limited duration (several hours to several weeks) and focus on the acquisition of discrete skills. Self-assessment is usually used in evaluation of these programmes [ 36 , 40 , 41 ], although some have implemented objective knowledge assessments [ 42 ]. While participants often demonstrate improved self-confidence [ 36 ], which has proven to be durable in some settings [ 40 ], other authors have not reported on the phenomenon of tempered self-confidence that we observed in a subset of our participants.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple medical subspecialties have successfully implemented boot camps at the medical school (69), residency (10, 11), and fellowship (12) training levels. A previous national survey assessed the efficacy of current radiation oncology resident orientations (22), with only 11.3% of respondents reporting that their orientation was essential.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies looked at the impact of introductory ''boot camps'' for new interns, with a multiday intervention that included didactics and clinic orientation/tours showing improvements in knowledge and clinical confidence. 22,23 The relatively limited number of published curricular interventions may be due to the large number of residency programs using extramural curricula (developed at outside institutions for broader use) 24 ; however, few groups published examinations of the implementation or impact of these modules in their individual residency programs. Additionally, very few curricula were published in MedEdPortal, limiting the ability to share curricular resources.…”
Section: Curriculum Developmentmentioning
confidence: 99%